PO100 Familial parkinson's disease in ireland. (1st December 2017) - Olszewska, Diana; McCarthy, Allan; Magennis, Brian; Ross, Owen; Lynch, Tim
Abstract : Objectives: To study the phenotype and establish the genetic background of familial Parkinson's disease (PD) in Ireland. Background: 10% of PD patients have a PD family history. Familial studies have led to the identification of causative gene mutations at 7 chromosome loci. Methods: We expanded upon a 12 year familial PD study and identified a further 174 familial cases. 98 patients were genetically tested for the known PD genes (McCarthy A, Ross O) (3 Parkin, no LRRK2 mutations). 76 new probands were recruited and 31 pedigrees were expanded. Results: In the analysis of 76 new pedigrees male to female ratio was 2.04, mean PD age-of-onset was 56.5 (range 29–80). Young onset PD (<age 50) occurred in 27.6%. Mean disease duration (symptom onset up to our assessment) was 7.88 years (1–31). Average UPDRS-III was 22.76. 75% of patients had tremor-predominant disease, 22.3%: postural instability and gait disorder and 2.6% mixed disease. PD dementia (MOCA <21) occurred in 7.89%, cognitive impairment (MOCA <26) in 19.73%, hallucinations in 9.21%. 51.31% had motor complications (wearing off: 21%, dyskinesia: 13.1%, freezing of gait: 11.8%) and 19.7% falls. Conclusion: LRRK2 mutations frequency varies geographically and are uncommon in Ireland. We will perform NGS to identify new PD genes.